Sin(альфа)-sin^3(альфа) =ctg 2(альфа) cos(альфа)-cos^3(альфа) cos(альфа+бета)+cos(альфа-бета) = сtg(альфа) sin (альфа+бета)+sin(альфа-бета)

Vikatop10 Vikatop10    1   17.05.2019 18:30    1

Ответы
Keksic0066 Keksic0066  10.06.2020 23:31

1)Sin(альфа)(1-Sin^2(альфа))/cos(альфа)(1-cos^2)(альфа)=ctg(альфа)

tg(альфа)*ctg^2(альфа)=ctg(альфа)

ctg(альфа)=ctg(альфа)

 

2)cos(альфа)*cos(бета)-sin(альфа)*sin(бета)+cos(альфа)*cos(бета)+sin(альфа)*sin(бета)/

cos(альфа)*cos(бета)+cos(альфа)*sin(бета)+sin(альфа)*cos(бета)-cos(альфа)*sin(бета)=

сtg(альфа)

2cos(альфа)*cos(бета)/2cos(альфа)*cos(бета)= сtg(альфа)

сtg(альфа)=сtg(альфа)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра